Enhancing Student Comprehension of Islamic Investment and Capital Market with PJBL Approach - Pratama, Aditya; Aprizal, Yusuf Zaini (Jurnal Ilmiah Ekonomi Islam, 2024)
The low level of financial literacy among the populace has resulted in many individuals falling victim to fraudulent investment schemes. Therefore, there is a crucial need for all segments of society, including the academic community, to play a role in enhancing investment literacy. The implementation of Project Based Learning (PBL) within the Investment and Sharia Capital Market course has demonstrated its effectiveness in equipping students with the knowledge, skills, and practical experience necessary to navigate the complexities of Islamic finance. By aligning course objectives with real-world applications and leveraging student autonomy and engagement, the PBL approach has empowered students to become agents of change in society. Through their participation in the course, students have not only gained a deep understanding of Sharia-compliant investment principles but have also developed critical analytical skills and practical experience in navigating the capital market. This multifaceted approach has prepared them to become consultants and researchers capable of promoting ethical and sustainable investment practices within society.